Efeitos da reposição estrogênica na cartilagem articular de fêmur de ratas diabéticas e ovariectomizadas - Fernandes, Alexandre Saeki [UNIFESP] (2016)
The degeneration of the articular cartilage is often observed in menopausal women, estrogen deficiency is one of the main causes of this degeneration. Furthermore, studies indicate that diabetes mellitus also causes negative effects on articular cartilage, however, the effects associated with the lack of estrogen, diabetes and estrogen replacement cartilage articulate are poorly understood. To assess the effects associated with the estrogen deficiency and diabetes (Di) and of estrogen replacement of articular cartilage in rats. Methods: 50 adult female rats at 3 months of age were ovariectomized (OVX) and after 21 days, divided in five groups: GI - (Ovx); GII (Ovx - treated with 10mg / kg per day of estrogen (Est) subcutaneously; GIII - (OVX + Di induced by streptozotocin (65?g / kg); GIV (OVX + Di + Est), GV - Sham-Di. After 60 consecutive days of treatment, animals were euthanized, the distal femurs containing articular cartilage collected and fixed in 10% formaldehyde buffered saline and embedded in paraffin. Sections (4?m in thickness) were stained with hematoxylin and eosin for histomorphometric analysis, submitted to histochemistry of red picrosirius (PS) for evaluation of collagen fibers and Alcian Blue (AB) for quantification of glycosaminoglycans (GAGs) and immunohistochemical methods cleaved caspase-3 and Ki67. Quantitative data will be statistically analyzed for comparison between groups (p<0.05). Results: We observed a smaller thickness of the articular cartilage and amount of glycosaminoglycans, more caspase-3 positive cleaved chondrocytes, birefringence of collagen fibers in GIII (Ovx-Di) compared the other groups. Conclusion: Our results demonstrate that diabetes combined with ovariectomy has a deleterious effect on the articular cartilage of rat femur. In addition, treatment with estrogen showed little or no impact on the measured parameters.